2020
DOI: 10.3389/fpsyg.2020.508141
|View full text |Cite
|
Sign up to set email alerts
|

Dispositional Self-Construal Modulates the Empathy for Others’ Pain: An ERP Study

Abstract: Previous studies have shown that temporal self-construal priming can modulate the empathic neural responses to others’ pain. However, little is known about the influences of the dispositional self-construal on empathic neural responses to others’ pain. The present study aimed to investigate neural correlates that underlie the modulation effect of dispositional self-construal on perception of others’ pain. Event-related potentials were recorded for pictures depicting the hands of strangers in painful or no-pain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 46 publications
2
3
0
Order By: Relevance
“…Through a moderated mediation analysis, we also found that this moderation solely impacts the indirect effect of outgroup embodiment via empathy. Findings thus extend past literature on how related constructs such as collectivism (Duan et al, 2008), interdependence (Cross et al, 2000;Chen et al, 2020), and social group awareness (Zhao et al, 2013) are conducive to empathic expression. Attaching importance to social identity may heighten one's propensity toward forging bonds and solidarity with others, thus enabling the prosocial benefits of empathy to manifest.…”
Section: Social Identity Orientation As a Moderatorsupporting
confidence: 83%
See 1 more Smart Citation
“…Through a moderated mediation analysis, we also found that this moderation solely impacts the indirect effect of outgroup embodiment via empathy. Findings thus extend past literature on how related constructs such as collectivism (Duan et al, 2008), interdependence (Cross et al, 2000;Chen et al, 2020), and social group awareness (Zhao et al, 2013) are conducive to empathic expression. Attaching importance to social identity may heighten one's propensity toward forging bonds and solidarity with others, thus enabling the prosocial benefits of empathy to manifest.…”
Section: Social Identity Orientation As a Moderatorsupporting
confidence: 83%
“…In a study by Duan et al (2008) cultural value placed on the social collective-predicted greater emotional empathy. Likewise, in a neurological ERP study, priming a view of the self as socially interdependent on other people stimulated stronger neural empathic responses to the pain of others (Chen et al, 2020). Taken together, these studies suggest that a SIO may facilitate the prosocial effects of empathy, but this relationship has yet to be examined in the context of embodiment and intergroup bias.…”
Section: Social Identity Orientationmentioning
confidence: 91%
“…Consistent with previous studies ( 35 39 ), the present study found that both behavioral (RTs, ACCs) and ERP (N1, N2, P2, P3, and LPP amplitudes) results were significantly modulated by the main effect of “Pain” as participants responded more quickly and more accurately, and showed larger ERP amplitudes to painful than to non-painful stimuli. In previous studies of empathy for pain, a subset of fixed ERP components have been shown to be good indicators.…”
Section: Discussionsupporting
confidence: 92%
“…Usually, both static and dynamic painful stimuli elicit N1, N2, P2, and P3, and late positive potential (LPP) components in ERP studies of empathy for pain. N1, N2, and P2 represent the early emotional component, while P3 and LPP represent the late cognitive component of empathy for pain ( 35 39 ). The early involuntary onset of pain empathy for emotion sharing and emotional contagion is reflected in early components, while late pain empathic processing, including pain recognition and judgment of self - others is reflected in late components ( 40 ).…”
Section: Introductionmentioning
confidence: 99%
“…Customers with an interdependent self‐construal tend to show greater satisfaction with relationships (Cross et al, 2000), foster cooperation (Galang et al, 2021; Utz, 2004), and initiate actions that support others and good causes (Simpson et al, 2020; Vaidyanathan et al, 2013; Winterich & Barone, 2011). They also express more empathy for others (Chen et al, 2020; Lalwani & Shavitt, 2009) due to their focus on interpersonal harmony and compassion for others (Hess et al, 2016; Kuppens et al, 2008). Therefore, an interdependent (vs. independent) self‐construal is more likely to exhibit a positive effect on service performance.…”
Section: Studymentioning
confidence: 99%